2017
DOI: 10.21105/joss.00091
|View full text |Cite
|
Sign up to set email alerts
|

Mordecai: Full Text Geoparsing and Event Geocoding

Abstract: Mordecai3 is a new end-to-end text geoparser and event geolocation system. The system performs toponym resolution using a new neural ranking model to resolve a place name extracted from a document to its entry in the Geonames gazetteer. It also performs event geocoding, the process of linking events reported in text with the place names where they are reported to occur, using an off-the-shelf question-answering model. The toponym resolution model is trained on a diverse set of existing training data, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 9 publications
1
44
0
Order By: Relevance
“…GeoTxt uses a search engine platform (Solr) to retrieve toponyms with a score computed based on string similarity as well as a variety of other feature weights. The initial computed scores can be fed into an algorithm (Halterman, ; Liu, ; Martins & Calado, ) to train a supervised machine learning model to find optimized weights for those features.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…GeoTxt uses a search engine platform (Solr) to retrieve toponyms with a score computed based on string similarity as well as a variety of other feature weights. The initial computed scores can be fed into an algorithm (Halterman, ; Liu, ; Martins & Calado, ) to train a supervised machine learning model to find optimized weights for those features.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…PlaceSpotter are not clear. Not included in this list are GeoParser.io (http://geoparser.io/) and Mordecai (Halterman, ). The implementation details of GeoParser.io (which is not free for use) are not known.…”
Section: Related Workmentioning
confidence: 99%
“…A recent study identified five geoparsing systems: GeoTxt, Geoparser, Yahoo! PlaceSpotter, CLAVIN, and TopoCluster [6]. Also the systems for recognizing geographical names and disambiguating toponyms for two data sets were tested.…”
Section: Research Results and Analysismentioning
confidence: 99%
“…In order to produce final usable event data, I also perform the final step of resolving the event location or locations to their geographical coordinates. To do so I use the Mordecai text geoparser (Halterman 2017), which uses a neural network trained on several thousand gold-standard resolved place names to infer the country of a location mention, then performs a fuzzy-string search over the Geonames gazetteer (Wick and Boutreux 2011) and selects the best location among the locations returned from the search.…”
Section: Application: Geolocating Offensives In Syriamentioning
confidence: 99%